Geophysical exploration for nickel sulphide deposits in the Yilgarn block, Western Australia - D. F. Pridmore; J. H. Coggon; D. J. Esdale; F. W. Lindman (The Institute of Materials, Minerals and Mining, 1984)
Almost all the presently viable nickel reserves in the Yilgarn Block contain nickel in a sulphide phase. Both volcanic peridotite- associated (VPA) deposits and intrusive dunite-associated (IDA) deposits are characterized by massive, matrix and disseminated sulphides (typically, pyrrhotite, pentlandite, pyrite, chalcopyrite, magnetite and other spinels), though in the IDA deposits the volume of disseminated sulphides is far greater than that in the VPA deposits. Potentially all geophysical techniques have application in the direct detection of these deposits'gravity for the detection of the dense massive and matrix ore; magnetics for the detection of magnetite and pyrrhotite in the ores; electromagnetics for the detection of the massive and matrix ore; and induced polarization for the detection of disseminated and to some extent matrix and massive ore. In practice the application of geophysical techniques is limited to a varying extent by (1) the relatively small size of an economic accumulation of sulphides, particularly the VPA deposits, (2) the extreme depth of weathering and lack of outcrop on the Yilgarn Block and (3) the abundance of geological noise or anomalous responses caused by sources other than economic mineralization.